ExeKaliBurr: uma Ferramenta Exploratória Auxiliar para o Levantamento de Informações em Pentests Web - Barros, Daniel R.; Pimenta, Saskya A.; Rocha, Lincoln S.; Monteiro, José M. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.235547, 2023)
The Pentest is one of the main approaches within the Offensive Security area, an important sector of Cybersecurity that seeks to improve the protection and reliability of virtual systems through proactive security checks. During the execution of a Pentest, the security professional carries out a series of steps to perform the procedures, and one of these steps is called the Information Gathering phase. This work proposes an exploratory tool capable of working together with security professionals to facilitate and automate the manual searches that are carried out during the execution of the Information Gathering phase, thus providing greater convenience during the completion of this stage.